2018
DOI: 10.3390/agronomy8090172
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Improving the WOFOST Model for Sunflower Simulation on Saline Soils of Inner Mongolia, China

Abstract: Monitoring and improving environmental stress in crops is vital for the sustainable development of agriculture and food security. Traditional experimental methods are costly and time-consuming, yet crop growth models focus mainly only on water and nutrient stresses. In this study, a new World Food Studies (WOFOST) model, WOFOST-ES, was developed by the addition of a general environmental stress factor (ES). To calibrate and validate WOFOST-ES, two-year micro-plot experiments and one-year field experiments with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…3). This phenomenon was similar to the effects of many other environmental stresses on crop growth [56][57][58][59][60]. For instance, Helms et al [61] found that soybean seedling emergence was seriously affected only when water stress lasted 12 days.…”
Section: Discussionsupporting
confidence: 59%
“…3). This phenomenon was similar to the effects of many other environmental stresses on crop growth [56][57][58][59][60]. For instance, Helms et al [61] found that soybean seedling emergence was seriously affected only when water stress lasted 12 days.…”
Section: Discussionsupporting
confidence: 59%
“…SWAP simulates plant growth through the integration of the WOFOST cropping model (de Wit et al., 2019; Kroes et al., 2017; Kroes & Supit, 2011). WOFOST does not, however, explicitly consider the effects of salinity as a limitation on plant growth, thereby limiting the integrated models ability to predict the effects of changing salinity on plant health (J. Zhu et al., 2018). Likewise, RZWQM2 integrates the DSSAT model for plant growth, but the version of DSSAT used by RZWQM2 does not include the effects of salinity (Jones et al., 2003).…”
Section: Dynamical Modelsmentioning
confidence: 99%
“…For this reason, crop modeling has increased appreciably in recent decades (Murthy, 2004;Di Paola et al, 2016). In general, many models have been developed for simulating the soil-plant system, some of them are based on soil hydrology, such as HYDRUS and SWAT, which just consider the environmental stress (water, nutrients, and heat), and many others are based on the physiology of plants (such as APSIM and WOFOST), which consider the crop growth process and pay less attention to the applied stress on plants (Zhu et al, 2018). The plant growth modeling requires the initial parameters of the plants as inputs.…”
Section: Introductionmentioning
confidence: 99%